“Effectiveness of Foot Reflexology on Post-Caesarean Pain Among Mothers Admitted In Selected Hospitals at Kolhapur” - Miss. Parineeta Vikram Chopade; Manisha Bijapurkar; Chandrala S. Patole, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background and Objectives Caesarean section rates are rising globally, with 25.4% of deliveries in Maharashtra, India, performed via caesarean section. Post-caesarean pain is a significant concern, often requiring effective management to enhance recovery and maternal satisfaction. Non-pharmacological interventions like foot reflexology offer a safe, cost-effective alternative to pharmacological methods. The researcher aims to assess the post caesarean pain among mothers admitted in Dr. D. Y. Patil Medical College Hospital and Medical Research Institute, Kolhapur. The study seeks to understand the effectiveness of foot reflexology on post caesarean pain among mothers. Objectives: The present study is aimed that to assess effectiveness of foot reflexology on post-caesarean pain among mothers admitted in selected hospitals at Kolhapur. The objectives are as follows, 1. To assess the post caesarean pain among mothers in experimental and control group. 2. To evaluate the effectiveness of foot reflexology on post caesarean pain among mothers. 3. To compare the post-test pain scores among mothers between experimental and control group. 4. To find out an association between pre-test pain scores of mothers with their selected socio demographic variables in experimental group and control group. Methods: A quasi-experimental pre-test post-test control group design was used, involving 74 post-caesarean mothers (37 experimental, 37 control) was selected by using non probability purposive sampling technique. The experimental group received foot reflexology (10 minutes per feet, daily for 5 days, while the control group received hospital routine care. Pain was assessed on 6th post operative day by using the visual analogue pain scale (VAS). Data was analysed using descriptive statistics, paired and unpaired t-tests, and chi-square tests. Result: In the experimental group, 51.4% had minor pain (VAS 1–3) and 48.6% had moderate pain (VAS 4–6) posttest, compared to 100% moderate pain pre-test. The control group showed no change (100% moderate pain). The mean post-test pain score was significantly lower in the experimental group (2.89 ± 1.2) than the control group (4.89 ± 0.8; t=8.32, p<0.001). No significant association was found between pre-test pain scores and socio-demographic variables (p>0.05). Interpretation and Conclusion: The study concludes that foot reflexology significantly reduces post-caesarean pain, offering a practical, non-pharmacological intervention for maternal care. Its integration into nursing practice is recommended to improve patient outcomes. The findings have implications for nursing practice, education, administration, and research.